Disorders of gastric function: gastroparesis and functional dyspepsia 2 - Kuo, Braden (Henry Stewart Talks, 2020)
Symptoms of functional dyspepsia, Dyspepsia subgroups, PDS and EPS, Diagnosis of functional dyspepsia, Treatment strategy and options for functional dyspepsia, H. pylori eradication, Proton pump inhibitors, Evidence for prokinetic therapies, Serotonergic agents, Selective serotonin reuptake inhibitors, Non-pharmacological treatments, Psychotherapy, Herbal remedies